The Self-Efficacy Scale in Academic Life: Psychometric Properties in New Students to the University Level - García-Méndez, Rosa María (2021)
This research article aimed to develop an instrument for measuring self-efficacy in academic life (SAL) of students, defined as the set of psychological, social, economic, and academic aspects directly or indirectly associated with the students’ academic life. Under a non-experimental, descriptive, correlational design, and with a sample of 2926 new students (55.1% women) to university education, the psychometric qualities of a set of SAL indicators were explored. The information was collected using a questionnaire form implemented via computer. This instrument comprised 102 items distributed in 14 factors that explained 59.5% of the variance with alpha reliability between .77 and .90 for the factors and .89 for the whole structure. The scale obtained an adequate concurrent validity with respect to the Self-efficacy scale in academic conduct when reaching favorable correlations between .40 and .60. The self-efficacy scale in academic life (SSAL) results also has percentile values in each of its subscales and cut-off values with high reliability set at the 25th percentile, which allows identifying subjects at risk. Low levels of self-efficacy have been reported associated with school dropouts and low academic performance. Focused as a diagnostic support instrument for university tutoring, the SSAL can help prevent adaptive problems in new students at the university level.